2013
DOI: 10.4103/0972-124x.107485
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenesis imperfecta and localised aggressive periodontitis: A rare clinical entity

Abstract: This case report presents two female patients whose chief complaint was discoloration of teeth. On careful clinical examination it was found that the patients had features of amelogenesis imperfecta and localised aggressive periodontitis. This article will give an insight of clinical and radiographic features of amelogenesis imperfecta with localised aggressive periodontitis, which is a rare clinical entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Some authors have reported that genetic mappings can be a useful tool in identifying to which AI group a patient belongs. [9][10][11][12] First, one has to exclude the presence of systemic diseases that may show generalized enamel hypoplasia. Secondly, it enables affected families to seek genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that genetic mappings can be a useful tool in identifying to which AI group a patient belongs. [9][10][11][12] First, one has to exclude the presence of systemic diseases that may show generalized enamel hypoplasia. Secondly, it enables affected families to seek genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Several untoward events may disrupt proper enamel formation including poor nutrition, trauma, and infections both pre-and post-natal. Amelogenesis imperfect is a term used to describe a wide range of hereditary enamel defects, and can be generally subdivided into hypoplastic, hypomaturation and hypocalcification forms, with different histological and often clinical characteristics for each (Witkop 1957;Gundannavar et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Amelogenesis imperfect is a term used to describe a wide range of hereditary enamel defects, and can be generally subdivided into hypoplastic, hypomaturation and hypocalcification forms, with different histological and often clinical characteristics for each (Witkop ; Gundannavar et al. ).…”
Section: Discussionmentioning
confidence: 99%